Reading habits in students of the first year community of educational psychology of the Universidad Pedagógica Nacional (UPN), Mexico - Izquierdo Dorantes, Martha Lorena (2020)
The objective of this research was to identify reading habits in three groups of first semester students of the Bachelor in Educational Psychology of the National Pedagogical University Unit Ajusco in Mexico City. This study had a descriptive scope with a non-experimental design in which 69 students participated, of which 60 were women and 9 men with an average age of 20 years, whose selection was made under a non-probabilistic sampling for accessibility and availability of the teacher responsible for the groups. To obtain the data, the Reading Habits Questionnaire was used, which was applied in the classroom of each of the programmed groups and for the information processing the Excel 2013 version software was used. The results showed that the students analyzed in this study, although they read periodically do not have the habit, it was also found that the book is still the main source of information in both the printed and digital format.